Extracellular Matrix Protocols - Streuli, Charles H; Ed (Humana Press, 2000)
t is now widely accepted that much of the dynamic function of cells and tissues is regulated from outside the cell by the extracellular matrix (ECM). In Extracellular Matrix Protocols, leading bench-top experimentalists from around the world present in a proven format their state-of-the-art methods for probing the extracellular matrix, its mechanisms of assembly, and how it influences cell behavior. These carefully detailed biochemical, biophysical, molecular biological, and cell biological techniques have been optimized for the study ECM structure and assembly, the mechanisms of cell-ECM interactions, and the molecular genetics of ECM proteins and defects in human disease, and bring to a wider audience a range of highly sophisticated methods that have hitherto been difficult even for a few specialized laboratories. Cutting-edge and highly practical, Extracellular Matrix Protocols offers today's ECM researchers a gold-standard collection of powerful, readily reproducible methods to investigate the extracellular matrix and the altered cell-ECM interactions that play so important a role in human health and disease.